Abundance and densities of beaked and bottlenose whales (family Ziphiidae) - Barlow , Jay; Ferguson , Megan C.; Perrin , William F.; Ballance , Lisa; Gerrodette, Tim; Joyce , Gerald; MacLeod , Colin D.; Mullin , Keith; Palka , Debra L.; Waring, Gordon (J. Cetacean Res. Manage., 2023)
Estimating the abundance and density of beaked whales is more difficult than for most other cetacean species. Consequently few estimates appear in the published literature. Field identification is problematic, especially for the smaller species, and visual detection rates decrease dramatically with Beaufort sea state; prior experience is very important to an observer’s ability to detect beaked whales. Passive acoustics may hold future promise for detecting beaked whales from their vocalisations, especially for the larger species. Most published estimates of abundance or density are based on visual line-transect studies that found narrower effective strip widths and lower trackline detection probabilities for beaked whales than for most other cetaceans. Published density estimates range from 0.4-44 whales per 1,000km2 for small beaked whales and up to 68 whales per 1,000km2 for large beaked whales. Mark-recapture methods based on photo-identification have been used to estimate abundance in a few cases in limited geographical areas. Focused research is needed to improve beaked whale abundance and density estimates worldwide.